Leadership Development in Context: Insights and Best Practices from Global Organizations - Yusoff, Asrif (Universitas Gadjah Mada, 2025)
Introduction/Main Objective: This study explores the diverse leadership development practices of three global organisations to identify effective strategies and their alignment with organisational performance. Background Problems: Leadership development is recognised as critical for organisational success, yet approaches vary widely across industries and regions, requiring contextual alignment with workforce needs. Novelty: The paper contributes by comparing leadership development strategies in diverse organisational contexts, and linking them to Adult Learning Theory (ALT) and Self-Determination Theory (SDT) to explain how adults learn and sustain motivation in leadership training. Research Methods: A document-based comparative analysis was conducted using secondary public data from academic literature, industry reports, and company sources. The analysis focused on three multinational organisations known for pioneering and innovating leadership development practices. Finding/Results: Findings show that successful leadership development is contextualised, incorporates experiential learning, and leverages digital technologies. Organisations emphasise alignment with strategic goals and a blend of formal and informal learning to strengthen engagement and long-term effectiveness. Conclusion: Effective leadership development requires strategic alignment with organisational goals, some level of personalisation to ensure relevance and engagement, and blended approaches that combine the best methods that suit the targeted demographic. These practices enhance sustainability of leadership pipelines and provide models for organisations to emulate.